Validation of the JAMR F1701T (arm type) pressure monitor according to the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/ISO 81060-2:2018 protocol. Issue 3 (7th June 2023) - Li, Jing; Han, Li-Hong; Feng, Ru; Wu, Li-Hao; Cai, Jie; Zeng, Tian-Ying; Liu, Hui; Zeng, Ya-Wen; Zhou, Li; Zhan, Zhong-Qun
Abstract : To validate the JAMR F1701T (arm type) blood pressure (BP) monitor according to the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization (AAMI/ESH/ISO) Universal Standard (ISO 81060-2:2018). A total of 90 subjects (male 60 and female 30) were recruited to fulfill the criteria of the AAMI/ESH/ISO Universal Standard (the number, gender, age, limber size, and BP distribution), and sequential measurements of BP, including both SBP and DBP were obtained using the test device and the standard mercury sphygmomanometer. A total of 270 sets of comparison data (three sets of each subject) were obtained and analyzed. According to the validation criterion 1 of ISO 81060-2:2018, the mean ± SD of the differences between the JAMR F1701T and mercury sphygmomanometer BP (systolic/diastolic) readings was 2.06 ± 6.83/−4.84 ± 5.23 mmHg. For criterion 2, the SD of the averaged BP (systolic/diastolic) differences between the JAMR F1701 and reference BP (systolic/diastolic) per participant was 5.62/4.39 mmHg (the requirement was ≤6.43/5.01 mmHg by calculation). The JAMR F1701T met all the requirements of the ISO 81060-2:2018, and can be recommended for clinical and self/home use.